Identifikasi Self Regulated Learning dalam Proses Belajar Daring Mahasiswa Bimbingan dan Konseling - Mukhromah, Armitha; Putri, Rani Mega; Sucipto, Sigit Dwi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
This study aims to identify aspects of self-regulated learning in the learning process of Guidance and Counseling students at Sriwijaya University. This research is a basic research and uses a quantitative descriptive method. The population of this study were Guidance andCounseling undergraduate students from the 2018-2021 Faculty of Teacher Training and Education, Sriwijaya University. The sampling technique used in this study is a purposive sample or a purposive sample. The sample in this study was Guidance and Counseling Students Batch 2021 with a total of 89 students as respondents. The results of data analysis carried out showed that 89% of students were at a high SRL level and 11% at a moderate level, in the analysis of each aspect the cognitive and psychomotor aspects were in the high category while the affective aspects were in the medium category.